The Request for Postponement of the Blashphemy Case Criminal Charge Reading by Police and Prosecutors - Mohd Andalusia Masri; Dahlan Ali; Darmawan Darmawan (Kanun Jurnal Ilmu Hukum, 2021)
This research aims to evaluate the police's request to postpone the criminal charge reading of the blasphemy case at the North Jakarta District Court, which was not based on Indonesia's positive law. The request to postpone a trial by the police without a legal basis could be considered a form of police intervention against the trial process, which has legal criminal consequences based on Article 3 Paragraph 2 and 3 of Law Number 48 of 2009 concerning Judicial Power. Meanwhile, the request for a two-week trial postponement by the public prosecutors due to their inability to complete the criminal indictment, as well as considering the request from the police, has created an impression that the public prosecutors have complied with the request of the police. It also injured public trust that demanded a fair and transparent law enforcement process.